2012
DOI: 10.1007/s00234-012-1005-0
|View full text |Cite
|
Sign up to set email alerts
|

Education increases reserve against Alzheimer’s disease—evidence from structural MRI analysis

Abstract: IntroductionThe aim of this study was to determine whether years of schooling influences regional cortical thicknesses and volumes in Alzheimer’s disease (AD), mild cognitive impairment (MCI), and healthy age-matched controls.MethodsUsing an automated image analysis pipeline, 33 regional cortical thickness and 15 regional volumes measures from MRI images were determined in 121 subjects with MCI, 121 patients with AD, and 113 controls from AddNeuroMed study. Correlations with years of schooling were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
125
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(136 citation statements)
references
References 46 publications
8
125
1
2
Order By: Relevance
“…Recently, it has been demonstrated that those individuals with more educational years show increased cerebral anales de psicología, 2016, vol. 32, nº 1 (enero) connectivity and more regional volume of the cerebral cortex (Arenaza-Urquijo et al, 2013;Liu et al, 2012). Among Alzheimer's disease patients, more education has been associated with a faster decline in certain cognitive domains, such as abstract reasoning, but at the same time it may help to conserve other cognitive performance (Le Carret et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that those individuals with more educational years show increased cerebral anales de psicología, 2016, vol. 32, nº 1 (enero) connectivity and more regional volume of the cerebral cortex (Arenaza-Urquijo et al, 2013;Liu et al, 2012). Among Alzheimer's disease patients, more education has been associated with a faster decline in certain cognitive domains, such as abstract reasoning, but at the same time it may help to conserve other cognitive performance (Le Carret et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Une étude s'intéressant à l'épaisseur corticale rapporte des résultats assez similaires à ceux retrouvés en VBM. Le gyrus temporal transverse, l'insula et l'isthme du cortex cingulaire étaient plus épais chez les personnes âgées saines avec une réserve élevée [13]. Néanmoins, ces précédents résultats sont à comparer avec ceux d'une étude indiquant qu'un haut niveau de scolarité était associé à la présence d'un cortex plus fin au niveau des régions occipitales latérales droites, temporales moyennes droites et entorhinales gauches [10].…”
Section: Les Modèles Passifs De La Réserve Ou Réserve Cérébraleunclassified
“…Structural MRI parameters and CR proxies suggest that, among healthy elders, higher CR scores relate to better preserved global and regional cerebral brain volumes [8]. However, the correlation between CR and brain volume was demonstrated to be negative in Alzheimer's disease (AD) patients populations [4]. In particular, when AD groups were analyzed, the more KEYWORDS: 18 F-fluorodeoxyglucose n Alzheimer's disease n amyloid PET n brain PET n cognitive reserve educated patients demonstrated smaller regional cortical thickness in the temporoparietal cortex than patients with less education [4,8].…”
mentioning
confidence: 98%
“…In particular, neuro psychological and clinical evaluations are sensitive to brain injury and dysfunction, but they lack precise anatomical localization. Therefore, to better understand CR, several studies have been carried out using neuroimaging approaches [2][3][4][5][6]. In these studies, CR has been defined as the difference between an individual's expected cognitive performance, measured by the level of imaging-assessed brain damage, and their actual cognitive performance.…”
mentioning
confidence: 99%